2020
DOI: 10.3390/jcm9051321
|View full text |Cite
|
Sign up to set email alerts
|

Smoking and SARS-CoV-2 Disease (COVID-19): Dangerous Liaisons or Confusing Relationships?

Abstract: We read with great interest the article by Brake SJ and colleagues [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 15 publications
0
9
0
1
Order By: Relevance
“…20,25,27,50 While it is highly unlikely for the majority of cigarette smoke compounds to have any potential benefit considering their toxic characteristics and oxidative stress and inflammation-promoting properties, some researchers have hypothesized that these findings might imply a protective effect of nicotine. [50][51][52][53] It was recently reported that many of the clinical manifestations of COVID-19 could be explained by a dysfunction of the nicotinic cholinergic system, and it was hypothesized that nicotine could modulate the immune response by restoring the function of the cholinergic antiinflammatory pathway. 52 Severe COVID-19 appears to represent a hyper-inflammatory response that could result from dysregulation of the immune system and a failure to return to homeostasis after being activated to combat viral invasion.…”
Section: Discussionmentioning
confidence: 99%
“…20,25,27,50 While it is highly unlikely for the majority of cigarette smoke compounds to have any potential benefit considering their toxic characteristics and oxidative stress and inflammation-promoting properties, some researchers have hypothesized that these findings might imply a protective effect of nicotine. [50][51][52][53] It was recently reported that many of the clinical manifestations of COVID-19 could be explained by a dysfunction of the nicotinic cholinergic system, and it was hypothesized that nicotine could modulate the immune response by restoring the function of the cholinergic antiinflammatory pathway. 52 Severe COVID-19 appears to represent a hyper-inflammatory response that could result from dysregulation of the immune system and a failure to return to homeostasis after being activated to combat viral invasion.…”
Section: Discussionmentioning
confidence: 99%
“…No estudo de Brake et al (2020), os autores propõem que o receptor da enzima conversora de angiotensina 2 -ACE2-seja regulado positivamente no epitélio das vias aéreas dos fumantes, indicando que os fumantes podem ser mais suscetíveis à infecção pelo SARS-CoV-2 e possivelmente pela COVID-19. Estudos confirmam estas informações e tratam da expressão ampliada deste receptor em pneumócitos do tipo 2, não apenas no cigarro comum, como também nos cigarros eletrônicos (Cai et al, 2020;Olds & Kabbani, 2020;Smith et al, 2020;Volti et al, 2020). Acredita-se que este é o principal mecanismo associado à progressão da COVID-19 em pacientes tabagistas, e em breve devem surgir novos estudos que demonstrem intervenções neste mecanismo para o tratamento destes indivíduos.…”
Section: Resultsunclassified
“…A ssociation between smoking and coronavirus disease 2019 (COVID-19) prognosis is a subject of scientific dispute. [1][2][3] Even though smokers seem to represent a disproportionately small part of hospitalized patients, 3,4 a meta-analysis of Chinese studies did not show a significant association between smoking and the severity of COVID-19. 5 Farsalinos et al concluded that smoking is generally harmful, but nicotine may be considered as a treatment option for COVID-19 due to low prevalence of smokers among patients hospitalized in China.…”
Section: Introductionmentioning
confidence: 96%